Phase I study of intratumoral administration of CV8102 in patients with advanced melanoma, squamous cell carcinoma of the skin, squamous cell carcinoma of the head and neck, or adenoid cystic carcinoma - Eigentler, Thomas; Thomas, Ioannis; Samoylenko, Igor; Erdmann, Michael; Heinzerling, Lucie; Ochsenreither, Sebastian; Krauß, Jürgen; Oberoi, Arjun; Robert, Caroline; Lebbe, Celeste; Martin-Liberal, Juan; Koch, Lukas; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background CV8102, a toll-like receptor 7/8 and RIG I agonist, has demonstrated antitumor immune responses in preclinical studies. We investigated intratumoral (IT) administration of CV8102 in patients with anti-programmed cell death protein-1 (PD-1) therapy-naïve or anti-PD-1 therapy-refractory cutaneous melanoma (cMEL) and in patients with advanced cutaneous squamous cell carcinoma, head and neck squamous cell carcinoma and adenoid cystic carcinoma.Methods This open-label, cohort-based, phase I dose escalation study aimed to establish the maximum tolerated dose (MTD), recommended dose (RD), safety and preliminary efficacy of CV8102 as monotherapy or in combination with a PD-1 inhibitor. The preliminary efficacy of the RD was assessed in patients with cMEL in the expansion cohorts.Results Between September 2017 and October 2022, 98 patients were enrolled in monotherapy and combination therapy dose escalation and dose expansion cohorts. Two patients in the CV8102 monotherapy dose escalation cohort experienced relevant toxicities at the 900 µg dose level. One patient had Grade 3 aspartate transaminase/alanine aminotransferase elevation which met dose-limiting toxicity (DLT) criteria. Another patient experienced Grade 3 immune-mediated pneumonitis. No DLTs occurred in the combination therapy dose escalation cohort. The MTD was not formally reached and the RD for expansion was 600 µg. Common treatment-emergent adverse events were fever (57%), chills (37%) and fatigue (25%). In the dose escalation part, objective responses occurred in 3/33 patients treated with CV8102 as monotherapy and in 2/25 patients treated with CV8102 plus a PD-1 inhibitor. In the expansion cohorts in patients with anti-PD-1 therapy-refractory melanoma, 0/10 patients treated with CV8102 as monotherapy and 5/30 patients (17%) treated in combination with a PD-1 inhibitor experienced objective responses.Conclusions IT CV8102 was generally well tolerated with preliminary signs of efficacy as monotherapy and in combination with a PD-1 inhibitor.Trial registration number NCT03291002.
Gesehen am 23.10.2025